Nistagmo posicional downbeat: Uma revisão narrativa - Rego, Angela; Sousa, Francisco; Feliciano, Telma; Almeida e Sousa, Cecília (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2021)
Objectives: To review the pathophysiology, differential diagnosis and treatment of central and peripheral positional downbeat nystagmus. Study design: Narrative review. Material and Methods: A search on “positional downbeat nystagmus” based on evidence presented in peer-reviewed journals was conducted on Pubmed® and ScienceDirect®databases. Reference lists of retrieved articles were manually searched to identify further relevant literature, including reference books. Results and Conclusions: Positional downbeat nystagmus is a rare entity attributed either to central pathology, for example posterior cerebellar lesions close to the midline, especially if the flocculus and paraflocculus are involved or the result of APC or AC BPPV. Nystagmus characteristics may be not sufficient to distinguish between the two entities. The conversion into a typical posterior canal BPPV by liberatory manoeuvres is the only criteria to diagnose a definitely peripheral APC or AC BPPV.